Lesion distribution characteristics of deep infiltrating endometriosis with ovarian endometrioma: an observational clinical study - Hungling Kwok; Hongye Jiang; Tian Li; Huan Yang; Hui Fei; Li Cheng; Shuzhong Yao; Shuqin Chen (BMC, 2020)
Abstract Background To investigate the characteristics of deep infiltrating endometriosis (DIE) lesion distribution when associated with ovarian endometrioma (OEM). Methods The present study analyzed retrospective data obtained by the First Affiliated Hospital of Sun Yat-sen University, between June 2008 to June 2016. A total of 304 patients underwent laparoscopic surgery for complete removal of endometriosis by one experienced surgeon, and histological confirmation of OEM associated with DIE was conducted for each patient. Clinical data were recorded for each patient from medical, operative and pathological reports. Patients were then divided into two groups according to unilateral or bilateral OEM. Patients with unilateral OEM were subsequently divided into two subgroups according to OEM location (left- or right-hand side) and the diameter of the OEM (≤50 and > 50 mm). The distribution characteristics of DIE lesions were then compared between the groups. Results DIE lesions were widely distributed, 30 anatomical sites were involved. Patients with associated unilateral OEM (n = 184 patients) had a significantly increased number of DIE lesions when compared with patients with bilateral OEM (n = 120 patients; 2.76 ± 1.52 vs. 2.33 ± 1.34; P = 0.006). Compared with bilateral OEM with DIE, there was a higher rate of intestinal (39.1% vs. 18.3%; P < 0.01) and vaginal (17.4% vs. 6.7%; P < 0.01) infiltration by DIE lesions in unilateral OEM with DIE. The mean number of DIE lesions was not significantly correlated with the location or size of the OEM (2.83 ± 1.56 vs. 2.74 ± 1.53; P = 0.678; and 2.65 ± 1.42 vs. 2.80 ± 1.43; P = 0.518, respectively). There was no significant difference between the groups with OEM ≤50 mm and > 50 mm. Conclusion Lesion distribution characteristics in women diagnosed with histologically proven OEM associated with DIE were frequently multifocal and severe.